2014
DOI: 10.1007/s00125-014-3306-9
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein P as a diabetes-associated hepatokine that impairs angiogenesis by inducing VEGF resistance in vascular endothelial cells

Abstract: Aims/hypothesis Impaired angiogenesis induced by vascular endothelial growth factor (VEGF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…This hypothesis, however, lacks support relevant to humans, in whom Se metabolism, as should be emphasized, is different when compared to animals [158]. This hypothetical approach is also notwithstanding with the recent in vitro study conducted in the human endothelial cells (HUVECS line), which suggests that overproduction of Sepp1 may lead to the impaired angiogenesis in diabetes type II [159]. 27 supplementation but also about establishing recommended dietary intake of the element based on maximization of GPx1 activity or Sepp1 expression.…”
Section: Biochemical Evidencementioning
confidence: 82%
See 1 more Smart Citation
“…This hypothesis, however, lacks support relevant to humans, in whom Se metabolism, as should be emphasized, is different when compared to animals [158]. This hypothetical approach is also notwithstanding with the recent in vitro study conducted in the human endothelial cells (HUVECS line), which suggests that overproduction of Sepp1 may lead to the impaired angiogenesis in diabetes type II [159]. 27 supplementation but also about establishing recommended dietary intake of the element based on maximization of GPx1 activity or Sepp1 expression.…”
Section: Biochemical Evidencementioning
confidence: 82%
“…Overall, caution must be used before advocating a maximal expression of Sepp1 by Se due to: 1) the growing evidence that in the laboratory studies Se-induced selenoprotein activity is at least in part an adaptive response to excess Se supply, taking into account that it is both Se-transport protein and antioxidant enzyme [208][209][210][211] strongly inducible by oxidative stress [181,212] 34 the ability of selenoproteins to increase following oxidative damage induced by several stressors in the absence of any increase in Se supply, a clear indication that the basal, steady state levels of selenoproteins do not reflect their potential maximal activity, and may authomatically increase as a compensatory response when required [181]; 3) the Se-induced upregulation of Se-independent antioxidant enzymes, such as catalase, type 1 superoxide-dismutase and Se-independent glutathione peroxidase [50, 169, 170, 172-175, 177, 213], an effect clearly indicative of a prooxidant effect of this element; 4) the indication from laboratory and human studies of possibly detrimental effect of high levels of Se-containing glutathione peroxidase and selenoprotein P [141,144,148,154,156,159,[162][163][164]; 5) the Se-induced increase in the human clusterin [128], a protein with unclear and dual role in the cancer initiation and progression [130] and more generally, the ability of Se to induce proteomic changes the biological significance of which is unexplored [60]; 6) the unclear association between Se and DNA damage, suggesting that Se supplementation may affect negatively DNA stability in the subjects with low baseline level of DNA damage, and that some Se compounds are able to decrease genomic stability by inactivating DNA repair proteins [214,215].…”
Section: Reassessing the Safe Range Of Se Exposurementioning
confidence: 99%
“…We first reported that circulating SeP level has an independent association with carotid intima-media thickness even after adjustment for other confounding factors [44]. Very recently, Ishikura et al [46] showed that physiological concentrations of SeP inhibited vascular endothelial growth factor-stimulated cell proliferation, tubule formation, and migration in human umbilical vein endothelial cells, leading to impaired angiogenesis and delay of wound closure in mice overexpressing SeP. Further studies are needed to explore the direct relationship between SeP with CVD and the underlying mechanism.…”
Section: Selenoprotein Pmentioning
confidence: 99%
“…Selenoproein P also impairs angiogenesis by inducing VEGF resistance in vascular endothelial cells (43).…”
Section: Selenoprotein P (In Humans Encoded By the Sepp1 Gene) Is Uprmentioning
confidence: 99%